Pregnancy and Peripartum Cardiomyopathy: Case Report - Çelik, Ebru Kavak; Gül, Evrim; Kavak, Salih Burçin (My University, 2016)
Peripartum cardiomyopathy is a rare but potentially life threating form of dilated cardiomyopathy of unknown etiology. Early diagnosis is important to decrease morbidity and mortality but delays in diagnosis are commonly observed because symptoms can be confused with physiological changes associated with advanced pregnancy. We herein report a case emerging in the postpartum period accompanied by preeclampsia and discuss the important issues in diagnosis and treatment.
Keywords: Genel ve Dahili Tıp; Kalp ve Kalp Damar Sistemi